Integrating Islamic Values into the 9E Learning Cycle: Effects on Students’ Self-Confidence in Science Education - Bella Satiyo Putri; Raicha Oktafiani (Yayasan Darussalam Bengkulu, 2025)
This study investigates the effects of integrating Islamic values into the 9E Learning Cycle model on students’ self-confidence in science education. A quantitative approach with a quasi-experimental pretest–posttest control group design was employed, involving two intact classes of secondary school students selected through cluster random sampling, where the experimental group received instruction using the Islamic-integrated 9E Learning Cycle and the control group was taught using conventional methods. Data were collected using a validated self-confidence questionnaire, observation sheets, and supporting documentation, and were analyzed through descriptive statistics, normalized gain (N-gain), independent samples t-test, Pearson correlation, and linear regression at a significance level of 0.05. The results revealed that the experimental group demonstrated a significantly higher improvement in self-confidence compared to the control group, with a moderate N-gain and statistically significant differences (p <0.05). Furthermore, correlation and regression analyses indicated a positive relationship between the instructional model and students’ self-confidence, with the model contributing meaningfully to variance in learning outcomes. These findings suggest that the integration of Islamic values within a structured constructivist framework effectively enhances students’ confidence by promoting active participation, reflective thinking, and meaningful engagement in science learning. In conclusion, the study confirms that a value-integrated inquiry-based model can simultaneously support affective development alongside cognitive processes in science education. The implications of this study highlight the importance of designing instructional approaches that integrate cultural and religious values with student-centered learning models to foster holistic educational outcomes, particularly in contexts where character development and academic achievement are equally prioritized.